Superiority of native seed core microbiomes in the suppression of bacterial wilt disease - Dong, Yanling; Gong, Jie; Yang, Lei; Jiang, Qipeng; Wen, Chengzhi; Zhang, Jidan; Yang, Ruiyu; Wang, Yao; Dai, Yuhao; Gao, Gui; Li, Shili; Cao, Yi; et al. (Frontiers in Microbiology, 2025)
IntroductionNative endophytic microorganisms in tobacco seeds are closely related to their resistance to Ralstonia solanacearum (R. solanacearum) infections. However, the role of the native seed core microbiome in the suppression of bacterial wilt disease (BWD) remains underexplored.MethodsThe characteristics of endophytic bacterial communities in both resistant and susceptible tobacco varieties were characterized using high-throughput sequencing technology.ResultsThis study found Paenibacillus as a potential microbial antagonist against BWD based on its significantly greater presence in BWD-resistant tobacco varieties, with a relative abundance that was 83.10% greater in the seeds of resistant tobacco than in those of susceptible varieties. Furthermore, a Paenibacillus strain identified as Paenibacillus odorifer 6036-R2A-26 (P. odorifer 26) was isolated from the seeds of the resistant variety. Following irrigation treatment with P. odorifer 26, the BWD index was reduced by 51.08%. Additionally, this strain exhibited significant growth-promoting effects on tobacco. It significantly increased the fresh weight of the tobacco plants by 30.26% in terms of aboveground weight, 37.75% in terms of underground weight, and 33.97% in terms of aboveground dry weight. This study highlights the critical role of Paenibacillus in tobacco seeds in the suppression of BWD, which may result from its antagonistic and growth-promoting properties.DiscussionThe results of this study revealed differences in the structural characteristics of endophytic bacterial communities between resistant and susceptible tobacco varieties, with groups such as Paenibacillus potentially playing significant roles in resisting BWD. These findings highlight the superiority of seed endophytic microorganisms. In the context of declining plant disease resistance and the spread of bacterial wilt, core endophytic microorganisms in seeds may emerge as a viable option for enhancing the productivity of agricultural ecosystems.